The Effect Of Asmaul Husna Dhikr On Blood Pressure In Hypertension Patients Pre-Anesthesia At Yogyakarta Islamic Hospital PDHI - Az Zahra, Hana; Azizah, Aisyah Nur; Rosidah, Istiqomah (Jurnal Kesmas Prima Indonesia, 2025)
Increased blood pressure during pre-anesthesia if not treated will cause bleeding both intra and post-operatively.Furthermore, it also increases the anesthetic dose, which prolongs the patient's recovery period after anesthesia. One therapy that can lower blood pressure is the recitation of the Asmaul Husana (Asmaul Husana) because it has a relaxing effect on the body.This study aims to determine the effect of dhikr Asmaul Husana on blood pressure in pre-anesthesia hypertension patients at the Yogyakarta Islamic Hospital PDHI..This research method used a pre-experimental design with a one-group pretest-posttest design with the Wilcoxon test. The sample in this study were 54 pre-anesthesia patients with accidental sampling. The results of data processing using the Wilcoxon test obtained a p-value of 0.000 (p <0.05), which means Ha is accepted. These results indicate that there is an effect of dhikr Asmaul Husana on blood pressure in pre-anesthesia hypertensive patients at the Yogyakarta Islamic Hospital PDHI. Kata kunci: Dzikir Asmaul Husna, Tekanan Darah, Pre Anestesi